Fluorescence Analysis of Biocide Efficiency in Antifouling Coatings against Cyanobacteria - Orzechowska, Aleksandra; Czaderna-Lekka, Anna; Trtílek, Martin; Rusiniak, Piotr (International journal of molecular sciences, 2023)
This study focused on the antifouling effect of copper oxide (Cu2O)- and zineb-based coatings against Cyanothece sp. ATCC 51142 by analysing photosynthetic activity using chlorophyll fluorescence. The photoautotrophically grown cyanobacterium was exposed to toxic coatings over a short-term period of 32 h. The study showed that Cyanothece cultures are particularly sensitive to biocides (i) released from antifouling paints and (ii) exhibited by contact with the coated surfaces. Changes in the maximum quantum yield of photosystem II (FV/FM) were observed within the first 12 h of exposure to the coatings. Partial recovery of FV/FM in Cyanothece was revealed 24 h post exposure to a copper- and zineb-free coating. In this research, we proposed an analysis of the evaluation of fluorescence data to study the initial response of cyanobacterial cells to copper- and non-copper-based antifouling coatings formulated with zineb. We evaluated the dynamics of coating toxicity by determining the characteristic time constants of changes in the FV/FM. Within the most toxic paints studied, those formulated with the highest concentration of Cu2O and zineb, the estimated time constants were 3.9 times lower compared to the copper- and zineb-free paint. The use of zineb in copper-based antifouling coatings enhanced the toxic effect of paints and contributed to a faster decline in photosystem II activity in Cyanothece cells. The analysis we proposed, along with the fluorescence screening results, may be useful in evaluating the initial antifouling dynamic action against photosynthetic aquacultures.
Keywords: Ships; Biofouling; Photosystem II Protein Complex; dezinficiencia; lodě; photosystem II (PSII) efficiency; nátěrové hmoty; cyanobacteria; Paint; toxicity; antifouling coatings; Fluorescence; sinice; fotosystém II (proteinový komplex); bioznečištění; Disinfectants; Cyanothece; fluorescence; Cyanobacteria; chlorophyll fluorescence